2004
DOI: 10.1002/bit.10913
|View full text |Cite
|
Sign up to set email alerts
|

Aven and Bcl‐xL enhance protection against apoptosis for mammalian cells exposed to various culture conditions

Abstract: A balance between proliferation and cell death is critical for achieving desirable high cell densities in mammalian cell culture. In this study, we evaluate a recently discovered anti-apoptotic gene, aven, and examine its effectiveness alone and in combination with a member of the Bcl-2 family, bcl-xL. The commercially popular cell line, Chinese hamster ovary (CHO), was genetically modified to constitutively express aven, bcl-xL, and the two genes in combination. Cells were exposed to several model insults tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
77
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(84 citation statements)
references
References 33 publications
6
77
1
Order By: Relevance
“…Aven is broadly expressed and conserved in mammalian species (26). In addition, Aven enhances the protective antiapoptotic function of Bcl-xL in chinese hamster ovary cells (27). The present study demonstrated that 10 mM Gln up-regulates Aven expression and may therefore inhibit apoptosome formation and the endstep of mitochondrial-mediated apoptosis.…”
Section: Discussionsupporting
confidence: 54%
“…Aven is broadly expressed and conserved in mammalian species (26). In addition, Aven enhances the protective antiapoptotic function of Bcl-xL in chinese hamster ovary cells (27). The present study demonstrated that 10 mM Gln up-regulates Aven expression and may therefore inhibit apoptosome formation and the endstep of mitochondrial-mediated apoptosis.…”
Section: Discussionsupporting
confidence: 54%
“…The functionality of the majority of the pro-and anti-apoptotic genes have been studied, and in several instances, additive and/or synergistic effects have been obtained by combining the expression of two or more anti-apoptotic genes. For example, successful combination of antiapoptosis genes have been reported and include E1B-19K and Aven in BHK cells in perfusion culture (Nivitchanyong et al, 2007), Bcl-2 with Bag in hybridoma cells (Suzuki and Ollis, 1990), Bcl-XL and Aven in CHO (Figueroa et al, 2004), and Bcl-XL and XIAPD in CHO cell line (Sauerwald et al, 2006), to name a few. In each case, the addition of the second or third anti-apoptotic gene improved the viability and protection of the transfected cell line.…”
Section: Discussionmentioning
confidence: 99%
“…Inherent in current high density, protein-free mammalian cell cultures is the problem of cell death of which apoptosis can account for up to 80% in a typical fed-batch bioreactor, induced in response to insults such as nutrient and growth factor deprivation, oxygen depletion, toxin accumulation, and shear stress (Goswami et al, 1999). Apoptosis limits the maximum viable cell density, accelerates the onset of the death phase and potentially decreases heterologous protein yield (Chiang and Sisk, 2005;Figueroa et al, 2001Figueroa et al, , 2003Figueroa et al, , 2004Mastrangelo and Betenbaugh, 1998;Mercille and Massie, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…There are concerted efforts underway by several groups to identify genes that would best influence the performance of cells in culture using transcriptional and proteomic profiling (Wlaschin and Seth 2006;Smales et al 2004). To date, most metabolic engineering strategies reported entail transient and/or randomly integrated overexpression or knockdown (short hairpin RNA) constructs to confer resistance to apoptosis (Figueroa et al 2004), control growth characteristics (Mazur et al 1998;b) or modify the protein product (Wong and Yap 2006). In addition, most studies involve modifying the expression of a single gene.…”
Section: Current Limitationsmentioning
confidence: 99%